2000
DOI: 10.1038/sj.ijo.0801433
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of treatment with an ephedrine/caffeine mixture. The first double-blind placebo-controlled pilot study in adolescents

Abstract: OBJECTIVE: The present study was performed to investigate the ef®cacy and safety of a caffeineaephedrine (CE) mixture in obese adolescents. SUBJECTS: Thirty-two (maf 16a16) obese children were included into the study. They were treated by diet (calculated daily energy requirement minus 500 kcal) and either CE or placebo (PL) for 20 weeks in a randomized double-blind placebo-controlled trial. Those weighing less than 80 kg took one tablet three times (100 mga10 mg), whereas those weighing more than 80 kg took t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 7 publications
1
46
1
Order By: Relevance
“…However, most were not without side effects. While there were no side effects associated with the use of caffeine and ephedrine [57], Orlistat [13,54] and Metformin [34] were associated with gastrointestinal side effects (e.g. diarrhoea, abdominal discomfort) and two out of the three studies which tested Sibutramine reported undesirable increases in blood pressure [7,44].…”
Section: Pharmacotherapymentioning
confidence: 97%
See 1 more Smart Citation
“…However, most were not without side effects. While there were no side effects associated with the use of caffeine and ephedrine [57], Orlistat [13,54] and Metformin [34] were associated with gastrointestinal side effects (e.g. diarrhoea, abdominal discomfort) and two out of the three studies which tested Sibutramine reported undesirable increases in blood pressure [7,44].…”
Section: Pharmacotherapymentioning
confidence: 97%
“…Pharmacological agents, including Orlistat, a pancreatic lipase inhibitor which reduces fat absorption [13,54], Sibutramine, a neurotransmitter reuptake inhibitor which enhances satiety by inhibiting the reuptake of serotonin, norepinephrine and dopamine [7,37,44], Metformin, an anti-hyperglycaemic and insulinsensitising agent [34], and the combination of the thermogenic stimulants caffeine and ephedrine [57], have all been reported to reduce weight and/or BMI in adolescents. However, most were not without side effects.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Thus in human studies, the lowest dose of ephedrine tested, with and without caffeine, which produced an effect was 20 mg/person/day. An exception is the study of Molnár (2000) in which 100 mg ephedrine (origin unknown) combined with 10 mg caffeine did not influence haemodynamic parameters in children.…”
Section: Discussionmentioning
confidence: 99%
“…Ephedra is used principally in current Western herbal medicine as a treatment for asthma and hay fever, and for the acute onset of colds and flu. It also helps to raise blood pressure, cool fevers, and alleviate rheumatism [19]. The whole plant contains many compounds, some active, some inert, which in combination seems to act synergistically.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women should not use it. Other women may try it to initiate menstruation [17,19]. As a weight loss agent, ephedra has been commonly combined with caffeine; however, more recently the ephedra component has been replaced with bitter orange in US dietary supplements.…”
Section: Introductionmentioning
confidence: 99%